Ritualizing sacredness in math: profaneness in language arts and social studies. - Ensign, Jacque (The Urban Review, 1997)
This paper examines the effect of ritual in different elementary subjects. Lessons in math, language arts, and social studies were observed in public, private, and home school first and fifth grades. In observing these classes, this researcher noted that in all contexts, math lessons were taught very differently from social studies and language arts, confirming earlier work by Stodalsky. The rituals in how concepts were taught, and in how students and teachers related to each other, were very different in math lessons from in the other two subjects. In language arts and social studies lessons, students and teachers routinely shared personal out-of-school experiences, whereas they rarely did so in math lessons. Drawing on Bernstein's description of the sacredness of subjects and linking it to theories in economic anthropology, the author attempts to explain the isolation of school math and to question the level of intimacy and community in current math classes. © 1997 Human Sciences Press, Inc.
5 citations (Crossref) [2023-10-31] Citation Key Alias: pop00210 tex.type: [object Object]
Keywords: dept.edu